Mapping of Sharia Stock Performance Research: Bibliometric Analysis - Zahira, Silvia Nazma; Hasanah, Roudatul (Indonesian Scientific Journal of Islamic Finance, 2025)
This study aims to map trends and research patterns related to the performance of sharia stocks using bibliometric analysis. Sharia stocks have become an attractive investment instrument because they integrate financial aspects with Islamic ethical principles. Using data from accredited national journals, this study analyzed scientific publications from 2009 to 2023. The results show a significant increase in the number of studies, reflecting the growing interest in sharia-based investments. The analysis also identifies key themes in the literature, including the relationship of sharia stocks to macroeconomic indicators, corporate governance, and market stability. In addition, research gaps were found, especially in the exploration of the impact of fiscal and monetary policies on sharia stock indices. This study makes a significant contribution to the development of literature and provides insights for investors and policymakers to understand the potential and challenges of sharia stocks. Thus, this research is an important reference for further studies and development of the sharia capital market globally.